Negocjacje w dziedzinie rolnictwa w ramach Światowej Organizacji Handlu a Wspólna Polityka Rolna - Redakcja (Wydawnictwo Naukowe UAM, 2007)
The purpose o f the paper is to present the current state o f affairs in the agricultural negotiations o f the World Trade Organization, as well as its likely impact on the Common Agricultural Policy. The study is founded on the basis of the Draft modalities by C. Falconer, published on July 17lh, 2007. As it comes to the internal support, C. Falconer suggests the reduction o f OTDS by 75 or 85 % applicable to the EU. If the parties agree on the lower value o f the reduction, this part o f the deal will not require much effort from the EU to adapt the reformed CAP to the new WTO rules. The direct payment scheme introduced by the 2003 reform, classified to the “green box” , will not be concerned by the cuts. Equally, the new de minimis threshold is completely acceptable for the UE. On the contrary, the area o f negotiations concerning market access is much more demanding from the European point o f view. The current proposal on the tariff cuts goes far beyond the last official offer made by the EU in October 2005. At the same time, the future o f the safeguard clause is uncertain and the number o f sensitive products highly unsatisfactory. Provided that the agreement is concluded in its present form, a sharp increase o f import may occur. This in consequence will heavily affect the balance o f the European agricultural markets. As a result, the cuts o f internal prices, especially for sugar and dairy products will be necessary. Similarly, the decision concerning the elimination o f the export subsidies until 2013 will make the European exports hardly profitable, while benefits generated from regulating other export practices do not seem to balance o ff the efforts. The paper ends in a conclusion that even though the European Commission is bound by the obligation to keep its offers in the limits that allow to preserve the current CAP unchanged, due to the new WTO regulations, another reform o f the European agricultural policy may not be avoided in the near future.
WTO AGRICULTURAL NEGOTIATIONS AND THE COMMON AGRICULTURAL POLICY